Penyelenggaraan Seminar Literasi Digital “Cerdas Membaca, Kreatif Menulis, Bijak Bermedia Sosial” Pada Kegiatan Sasak Literatif 2025 di Desa Bentek, Kab. Lombok Utara - Putra, Sandi Justitia; Mandini, Denda Devi Sarah; Audina, Pin Kharisma; Husbuyanti, Irma El-Mira; Rusyada, Gozin Najah (Bakti Sekawan : Jurnal Pengabdian Masyarakat, 2026)
The digital era has changed people's communication patterns, but it has also increased vulnerability to hoaxes, misinformation, and disinformation, especially among groups with low digital literacy levels. This community service activity aims to improve the digital literacy of the people of North Lombok through a Digital Literacy Seminar with the theme "Smart Reading, Creative Writing, Wise Social Media Use." The activity was held on October 3, 2025, in Bentek Village, involving 40 participants consisting of schoolchildren, university students, teachers, parents, community leaders, and youth activists. The implementation method included interactive lectures, case studies, group discussions, and information verification practices using a lateral reading approach and source credibility evaluation. Evaluation was carried out through pre- and post-tests to measure improvements in participant understanding. The results showed a significant increase in digital literacy, with the average score of participants increasing from 60.4 in the pre-test to 84.5 in the post-test (an increase of 24.1 points). The highest increase occurred in the ability to identify hoaxes, from 58.2 to 86.5. Furthermore, understanding of social media ethics, digital footprints and online privacy, and the credibility of information sources also improved substantially. This activity not only enhanced participants' knowledge and skills but also encouraged a more critical and responsible approach to media use. This program contributes to strengthening public information resilience and has the potential to be developed through community-based digital literacy mentoring.